Relation between systemic cell ratios and indices with oxidative stress in the severity of asthma: a South Indian study - Tasneem Fatima; Rashmi Bhuwalka; Rabia Tahseen; Mohammad Parvez; Sravan Kumar; Parveen Jahan (The Egyptian Journal of Bronchology)
Abstract Asthma, a chronic respiratory disease, is characterized by inflammation and narrowing of bronchi, affecting 300 million people worldwide. Cellular markers neutrophil-to-lymphocyte ratio (NLR), eosinophils-to-lymphocyte ratio (ELR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), systemic inflammatory index (SII), and systemic inflammatory response index (SIRI) reported individually in the assessment of asthma. However, there is no comprehensive approach using correlation between these multiple markers and oxidative stress (OS) in assessing severity of the condition. For the present hospital-based study, blood samples were collected from 200 individuals containing equal number of asthma patients (61% severe, 39% non-severe) and healthy volunteers. Samples were processed for serum MDA (sMDA) and complete blood picture; cell based ratios and indices were calculated (NLR, ELR, PLR, MLR, SII, and SIRI). We found higher values for all the parameters in the asthma patients over healthy controls (p < 0.05) and PLR, SII, and sMDA between severe and non-severe cases. Receiver operating characteristic (ROC) curve analysis showed good area under curve (AUC), specificity and sensitivity (ELR > PLR > SII > NLR) in patient and controls and in severe and non-severe cases (PLR > SII > NLR). Serum MDA exhibited correlation with all ratios and indices except ELR in patient group while no correlation in severe group. These results are suggestive of association of systemic cellular markers with OS in patients over controls. Heightened sMDA in severe cases appears to be independent of circulating cellular markers. As asthma is a progressive disease, understanding the severity requires longitudinal studies to develop novel inexpensive management strategies.